Longer pregnancy and slower fetal development in women with latent "asymptomatic" toxoplasmosis - Kanková, Sárka; Flegr, Jaroslav (BMC infectious diseases, 2007)
BACKGROUND: The purpose of this study was to confirm that women with latent toxoplasmosis have developmentally younger fetuses at estimated pregnancy week 16 and to test four exclusive hypotheses that could explain the observed data. METHODS: In the present retrospective cohort study we analysed by the GLM (general linear model) method data from 730 Toxoplasma-free and 185 Toxoplasma-infected pregnant women. RESULTS: At pregnancy week 16 estimated from the date of the last menstruation, the mothers with latent toxoplasmosis had developmentally younger fetuses based on ultrasound scan (P = 0.014). Pregnancy of Toxoplasma-positive compared to Toxoplasma-negative women was by about 1.3 days longer, as estimated both from the date of the last menstruation (P = 0.015) and by ultrasonography (P = 0.025). CONCLUSION: The most parsimonious explanation for the observed data is retarded fetal growth during the first weeks of pregnancy in Toxoplasma-positive women. The phenomenon was only detectable in multiparous women, suggesting that the immune system may play some role in it.
Keywords: dospělí; Female; Fetal Development; růstová retardace plodu; Adult; Linear Models; ženské pohlaví; Toxoplasmosis, Congenital; parita; Time Factors; časové faktory; vývoj plodu; kongenitální toxoplazmóza; lidé; Parity; parazitární komplikace těhotenství; těhotenství; lineární modely; kohortové studie; Cohort Studies; retrospektivní studie; Ultrasonography, Prenatal; protilátky protozoální; Antibodies, Protozoan; Fetal Growth Retardation; Pregnancy; ultrasonografie prenatální; Retrospective Studies; Pregnancy Complications, Parasitic; Humans